Crystallization of Rhenium Salts in a Simulated Low‐Activity Waste Borosilicate Glass. Issue 4 (19th March 2013) - Riley, Brian J.; McCloy, John S.; Goel, Ashutosh; Liezers, Martin; Schweiger, Michael J.; Liu, Juan; Rodriguez, Carmen P.; Kim, Dong‐Sang; Jantzen, C.
<x xml:space="preserve">Abstract</x> This study presents the characterization of salt phases that formed on simulated low‐activity waste glass melts during a rhenium solubility study. This study with rhenium salts is also applicable to real applications involving radioactive technetium salts. In this synthesis method, oxide glass powder is mixed with the volatile species, vacuum‐sealed in a fused quartz ampoule, and then heated in a furnace. This technique restricts the volatile species to the headspace above the melt but still within the sealed ampoule, thus maximizing the concentration of these species that are in contact with the glass. Above the previously determined solubility of Re7+ in this glass, a molten salt phase segregated to the top of the melt and crystallized into a solid layer. This salt was analyzed with X‐ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, as well as wavelength dispersive spectroscopy and was found to be composed of alkali perrhenates (NaReO4, KReO4) and alkali sulfates. Similar crystalline inclusions were found in the bulk of some glasses as well.